Alturas de manejo para forrageiras do gênero Urochloa em sistema silvipastoril - Victor Augustus Vasconcelos de Oliveira (2020)
The objective with the work was to compare the response of Urochloa decumbens cv. Basilisk and Urochloa Brizantha cv. Marandu in monoculture and in silvopastoral system (SSP), and define which defoliation height is the most suitable for handling in SSP. Two experiments were carried out. In the first, four intermittent defoliation heights were evaluated for U. decumbens cv. Basilisk (20, 30, 40 and 50 cm) in the SSP and a defoliated control 20 cm in full sun, in a randomized block design with 4 repetitions. In the second experiment, four intermittent defoliation heights for U. brizantha cv. Marandu (25, 35, 45 and 55 cm) in two distances (2.5 and 5 m) from the trees in the SSP and with a bare leaf at 25 cm in full sun, in a randomized block design with 3 repetitions. The tree species used was eucalyptus (Eucalyptus sp. Clone I144). Structural characteristics, production and morphological composition were evaluated in both works and chemical composition in brachiaria grass. The comparison of the different management goals with the controls showed different results for each species. The accumulation, leaf production and volumetric density of Urochloa decumbens cv. Basilisk in monoculture is higher than in the silvopastoral system, regardless of the management goal used. The accumulation of forage and the percentage of leaves in the brachiargrass monoculture were 36.2 kg / ha.day and 59.81%, while in the SSP they were 22 kg / ha.day and 59.06%. The management goal of 50 cm within the SSP resulted in tillering similar to the monoculture and lower percentage of dead fodder, representing qualitative advantages in relation to the other management goals in SSP. The different management heights resulted in a reduction in ash content and an increase in non-fibrous carbohydrates in brachiaria grass. The accumulation, total dry mass, leaf dry mass and volumetric density of Urochloa brizantha cv. Marandu in monoculture were also higher than in the silvopastoral system, regardless of the management goal and the distance from the trees. The morphological composition and leaf stalk ratio of the marandu grass forage are not affected by the cultivation system, the management goals adopted and the distances studied, except in the management at 55 cm and 5.0 m from the trees, where the production of culms is greater. The 55 cm management goal within the silvopastoral system at 2.5 m from the trees resulted in tillering similar to the monoculture, but with a higher content of dead forage.